Cytotoxic activity of Green Zinc Selenide Nanoparticles Against Hep-G2 Cell Lines - Sabah N. Mazhir1 , Kadhim A. Aadim2 , Mohammad M. F. Al-Halbosiy3 ,Nisreen Kh.Abdalameer4 (Indian Journal of Forensic Medicine & Toxicology, 2021)
In the current study a new technique between the plasma physics, nanoparticle and Biotechnology,structured(ZnSe) prepared by cold plasma technique using atmospheric pressure plasmajet system, Znse NPs wereprepared from selenium nitrate and zinc metal sheets to reduce selenium toxicity. The structural and opticalproperties were characterized by X-ray diffraction (XRD) and absorbance measurements of ZnSe greenNPs. The liver cancer cell line (hepG2) was exposed to the ZnSe nanoparticles, and The percentage ofcytotoxicity was suppressed after 24, and48 from exposure, induced cytotoxicity is found to be 70.3% inhepG2 after exposed 48h ZnSe green nanoparticle, and the maximum cytotoxicity of the normal cell line(REF) was also examined 42.62% when exposure ZnSe nanoparticles and 16.6% when exposure ZnSe greennanoparticles.